Energy Resolution Studies in Simulation for the IDEA Dual-Readout Calorimeter Prototype - Andreas Loeschcke Centeno (Instruments, 2022)
Precision measurements of Z, W, and H decays at the next generation of circular lepton colliders will require excellent energy resolution for both electromagnetic and hadronic showers. The resolution is limited by event-to-event fluctuations in the shower development, especially in the hadronic system. Compensating for this effect can greatly improve the achievable energy resolution. Furthermore, the resolution can benefit greatly from the use of particle-flow algorithms, which requires the calorimeters to have a high granularity. The approach of dual-readout calorimetry has emerged as a candidate to fulfil both of these requirements by allowing to reconstruct the fluctuations in the shower development event-by-event and offering a high transverse granularity. An important benchmark of such a calorimeter is the electromagnetic energy resolution; a prototype of the IDEA calorimeter has been built for use in testbeams. In parallel, a simulation of this prototype has been developed in Geant4 for a testbeam environment. Here, we outline how this simulation was used to study the electromagnetic energy resolution and conclude that a resolution of <semantics>14%/<msqrt>E</msqrt></semantics> is achievable.